2014
DOI: 10.15274/nrj-2014-10027
|View full text |Cite
|
Sign up to set email alerts
|

Use of Apparent Diffusion Coefficient Values for Diagnosis of Pediatric Posterior Fossa Tumors

Abstract: We prospectively compared the ability of neuroradiologists to diagnose medulloblastoma with novice raters using only apparent diffusion coefficient (ADC) values measured on ADC maps. One hundred and three pediatric patients with pre-operative magnetic resonance imaging scans showing a posterior fossa tumor with histological verification were retrospectively identified from a ten-year period at a tertiary care medical center. A single observer measured the lowest ADC values in all tumors to determine the mean m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 20 publications
3
44
0
3
Order By: Relevance
“…46–48 Because of the heterogeneous nature of intracranial tumors, particularly gliomas, histogram analysis can be employed to better assess ADC metrics. 43,4951 Although some authors have demonstrated good correlation between cell density and ADC values based on stereotactic biopsy, the required postprocessing and overlap in ADC values between tumor grades limit the role of quantitative ADC in clinical practice.…”
Section: Conventional Magnetic Resonance Imaging Featuresmentioning
confidence: 99%
“…46–48 Because of the heterogeneous nature of intracranial tumors, particularly gliomas, histogram analysis can be employed to better assess ADC metrics. 43,4951 Although some authors have demonstrated good correlation between cell density and ADC values based on stereotactic biopsy, the required postprocessing and overlap in ADC values between tumor grades limit the role of quantitative ADC in clinical practice.…”
Section: Conventional Magnetic Resonance Imaging Featuresmentioning
confidence: 99%
“…Restricted diffusion may be present in highly cellular solid regions of tumor, though typically apparent diffusion coefficients in ependymoma are not as low as in medulloblastoma. 4,6 An example of a posterior fossa ependymoma in an adult is shown in Figure 3.…”
Section: Neurooncologymentioning
confidence: 99%
“…Ambas lesiones pueden presentarse en línea media, tener componentes sólidos y quísticos, y presentarse alrededor de los cinco años de edad. Sin embargo, poseen algunas características morfológicas que pueden ayudar a distinguirlos 13,14 . Imagenológicamente el meduloblastoma es hiperdenso en la TC, con estructura heterogénea en RM, hipointenso en secuencias ponderadas en T1, e iso o discretamente hiperintenso en secuencias T2, con calcificaciones en 10-20% y un componente necrótico o cistoídeo en el 50% de los casos.…”
Section: Introductionunclassified
“…La DWI por RM ha demostrado utilidad en la diferenciación de estos tumores mediante la comparación de los valores de coeficiente de difusión aparente (ADC) intratumorales 1,[12][13][14]17 . En diversos estudios se ha demostrado que el meduloblastoma posee valores de ADC más bajos que los del ependimoma 10 .…”
Section: Introductionunclassified